2010
DOI: 10.4103/0256-4947.67079
|View full text |Cite
|
Sign up to set email alerts
|

Terbutaline versus salbutamol for suppression of preterm labor: a randomized clinical trial

Abstract: BACKGROUND AND OBJECTIVE:Preterm labor (PTL) is a common medical problem during pregnancies and is associated with neonatal mortality and morbidity. Beta-adrenergic agonists are among the most commonly used tocolytic agents. The aim of this study was to compare the effectiveness, safety and adverse effects of terbutaline with those of salbutamol in the prolongation of pregnancy beyond 48 hours and until 37 weeks of gestation.PATIENTS AND METHODS:Two hundred women with PTL were randomly assigned to receive subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Similar to the authors’ present results, Motazedian et al reported that a 48-hour prolongation of pregnancy was achieved in 87% patients receiving terbutaline and 84% patients receiving salbutamol 10. Likewise, the study at Siriraj Hospital, Bangkok, Thailand, revealed that the success rate in threatened preterm labor inhibition for 12 hours with nifedipine was about 80% 11.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to the authors’ present results, Motazedian et al reported that a 48-hour prolongation of pregnancy was achieved in 87% patients receiving terbutaline and 84% patients receiving salbutamol 10. Likewise, the study at Siriraj Hospital, Bangkok, Thailand, revealed that the success rate in threatened preterm labor inhibition for 12 hours with nifedipine was about 80% 11.…”
Section: Discussionsupporting
confidence: 89%
“…Details of the characteristics of the trials and comparison of the quality of tocolytic studies retrieved are reported elsewhere 16. Twenty five trials contained a placebo arm (26%),27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 60 included beta mimetics (63%),27 28 29 31 34 35 36 37 39 43 46 48 50 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 29 included magnesium sulfate (31%),29 30 33 38 47…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, R-sal at a lower dose could have a potential in reducing its cardiotoxicity side effects. Additionally, an oral dose of 25mg/d salbutamol in pregnant woman for prevention of preterm labor has been reported by Motazedian[39]. Most importantly, selective stimulation of β2-adrenoreceptor is reported to antiapoptotic rather than cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%